2005
DOI: 10.1098/rspb.2005.3158
|View full text |Cite
|
Sign up to set email alerts
|

First-ever observations of a live giant squid in the wild

Abstract: The giant squid, Architeuthis, is renowned as the largest invertebrate in the world and has featured as an ominous sea monster in novels and movies. Considerable efforts to view this elusive creature in its deep-sea habitat have been singularly unsuccessful. Our digital camera and depth recorder system recently photographed an Architeuthis attacking bait at 900 m off Ogasawara Islands in the North Pacific. Here, we show the first wild images of a giant squid in its natural environment. Recovery of a severed te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 6 publications
1
37
0
1
Order By: Relevance
“…Kubodera and Mori (2005) revealed that a giant squid off the Ogasawara Islands in the North Pacific appeared at 900 m depth and swam up to 600 m to escape from a jig on which its tentacle was hooked. They reported that the water temperatures at 900 and 600 m depth were about 4 and 6°C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kubodera and Mori (2005) revealed that a giant squid off the Ogasawara Islands in the North Pacific appeared at 900 m depth and swam up to 600 m to escape from a jig on which its tentacle was hooked. They reported that the water temperatures at 900 and 600 m depth were about 4 and 6°C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] One such group, the squids (Mollusca: Cephalopoda: Teuthoidea), are remarkable in several aspects. In addition to having an exceptionally well developed brain, sensory systems and skin (for adaptive coloration) [19] , these swift agile predators [20] have eight flexible strong arms, two fast extensible tentacles, and strong malleable suckers, all of which are muscular hydrostats [21] .…”
mentioning
confidence: 99%
“…The whole tail of the specimen was most likely severed by a predator, rather than other means of injury (e.g. propeller of a vessel), given the preferences of giant squid to deep-water habitats (Kubodera & Mori, 2005) and visible patterns of tissue damage ( Figure 1A). Injuries at the mantle tip ( Figure 1A) suggest predation by a large animal, probably a sperm whale, as they are known to prey on giant squid and regularly occur within the region (Clarke, 1980;Jefferson et al, 1993;Mannocci et al, 2014), or possibly a great white shark (Carcharodon carcharias), which occasionally visit Reunion Island waters (Zuffa et al, 2002;Jaquemet, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Its biology and distribution remain obscure, despite recent technological advances, which allowed in-situ giant squid observations (Kubodera & Mori, 2005;Schrope, 2013), and numerous records from all major oceans (Nesis et al, 1985;Re et al, 1998;Cherel, 2003;Martins & Alvarez Perez, 2009;Winkelmann et al, 2013;Roper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%